If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(x + 8) + 5x(6 + -1x) = 9(12 + x) + -8(7 + -1x) Reorder the terms: 5x(8 + x) + 5x(6 + -1x) = 9(12 + x) + -8(7 + -1x) (8 * 5x + x * 5x) + 5x(6 + -1x) = 9(12 + x) + -8(7 + -1x) (40x + 5x2) + 5x(6 + -1x) = 9(12 + x) + -8(7 + -1x) 40x + 5x2 + (6 * 5x + -1x * 5x) = 9(12 + x) + -8(7 + -1x) 40x + 5x2 + (30x + -5x2) = 9(12 + x) + -8(7 + -1x) Reorder the terms: 40x + 30x + 5x2 + -5x2 = 9(12 + x) + -8(7 + -1x) Combine like terms: 40x + 30x = 70x 70x + 5x2 + -5x2 = 9(12 + x) + -8(7 + -1x) Combine like terms: 5x2 + -5x2 = 0 70x + 0 = 9(12 + x) + -8(7 + -1x) 70x = 9(12 + x) + -8(7 + -1x) 70x = (12 * 9 + x * 9) + -8(7 + -1x) 70x = (108 + 9x) + -8(7 + -1x) 70x = 108 + 9x + (7 * -8 + -1x * -8) 70x = 108 + 9x + (-56 + 8x) Reorder the terms: 70x = 108 + -56 + 9x + 8x Combine like terms: 108 + -56 = 52 70x = 52 + 9x + 8x Combine like terms: 9x + 8x = 17x 70x = 52 + 17x Solving 70x = 52 + 17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17x' to each side of the equation. 70x + -17x = 52 + 17x + -17x Combine like terms: 70x + -17x = 53x 53x = 52 + 17x + -17x Combine like terms: 17x + -17x = 0 53x = 52 + 0 53x = 52 Divide each side by '53'. x = 0.9811320755 Simplifying x = 0.9811320755
| 7(-6)(5)= | | 4z^2+3z-1=0 | | 2x^2-3y=32 | | -(z+7)+(5z+1)=5(z+1) | | 5x-19=3x+6 | | 3x(x+3)=24 | | 27x=33 | | 100-50= | | 8cosx-3=0 | | F(-1)=3x^3-5x^2-2x-5 | | 5x-2=125 | | 3x-7i=3(3x-7u) | | 8n+32=4(7n-7) | | (3a^3)(5a^2)= | | 2h=-3g+52 | | 2-3ln(x+1)=8 | | 3-2*-4=w | | 4(x+6)=6(x-2)+3x-4 | | y=2x^2-12x-19 | | (2x-1)+2(2x+6)=4x-1 | | (2p+3)(2p-3)=(2p+10)(2p-10)-91p | | 3h+13h=20-2 | | 6x+7=3x+8 | | 2x+3(x-2)=4x-24+2x | | 6*-2=r-5r | | 7(x-9)-5=-68 | | 6*-2=r | | 15x=482 | | 3y-1+y+35=7+7y+33-5y | | 8w+6w=82 | | (x-4)2=(x-2) | | 4-t=2xa+21 |